“Un combattente tenace ”: il cardinale Wyszyński raccontato dal «Corriere della Sera » (1950-1981) - Bellifemine, Onofrio (Załącznik Kulturoznawczy, 2021)
Stefan Wyszyński (1901-1981), cardinal, archbishop of Warsaw and Gniezno from 1948 to 1981, Primate of Poland, was one of the most important post-World War II personalities in Poland. He was the key person in establishing the relationship between the Church and the Communist regime for over thirty years. From 1950 to 1981, the "Corriere della Sera", one of the oldest and most prestigious Italian newspapers, wrote a lot about Wyszyński. This essay analyzes its work in a critical way, keeping in mind the historical period and the opinions of the Italian national press.